Personality profile of team handball referees at expert level - Dodt, M.; Fasold, F.; Memmert, D. (German Journal of Exercise and Sport Research, 2022)
Referees play a central role in every sport. Particularly at national level, referees must meet ever higher demands due to increasing professionalisation. While cognitive and conditional aspects have already been investigated intensively, personality traits of handball referees have so far only received little attention. In addition to a profound understanding of the game and knowledge of the rules, however, it is precisely the demands on referees` personalities that are becoming increasingly important. Individual differences in personality are related to job performance in sports, especially with regard to coping with pressure and stress. Thus, personality is considered an essential component of the performance profile of referees and is required in the context of efficient game management. In this study, the personality profiles of male handball referees at expert level (N = 163) were examined for the first time, using the German version of the Big Five Inventory 2 (BFI-2). Standard values of the German general population from a population survey were used for comparison. Referees scored higher values in extraversion, agreeableness, and conscientiousness and a lower value in negative emotionality. The results of this cross-sectional study provide initial insights into the personality of this group of referees and thus lay the foundation for further research. A study with referees from different performance levels or cultural backgrounds could provide information on whether the results of this study only apply to German handball referees at expert level or are valid for all handball referees.